Neurologic abnormalities in HIV-1 infected children in the era of combination antiretroviral therapy. - Lotus A van Arnhem; Madeleine J Bunders; Henriette J Scherpbier; Charles B L M Majoie; Liesbeth Reneman; Olivier Frinking; Bwee Tien Poll-The; Taco W Kuijpers; Dasja Pajkrt (PLoS ONE, 2013)
Background Pediatric HIV-1 infection is associated with neurologic abnormalities. In recent years, the neurological outcome of HIV-1 infected children has substantially improved with combination antiretroviral therapy (cART). However, data regarding the long-term effect of cART and neurologic outcome are limited. Methods In the Pediatric Amsterdam Cohort on HIV-1 study, 59 perinatally HIV-1 infected children were evaluated from 1992-2010. All children underwent neurological examination and neuro-imaging studies, including CT-scan and/or MRI imaging. Fisher exact and Kruskal-Wallis tests were used to compare clinical deviations of neuro-imaging studies with HIV-1 related parameters, including CD4(+) T cell count, HIV-1 viral load in blood and cerebrospinal fluid (CSF), and duration of cART as well as neurological examination. Results Abnormal neurologic examinations in these HIV-1 infected children included language impairment (22%), abnormal muscle tone (hyper/hypotonia) (14%) and delay in reaching developmental milestones (12%). Ventricular enlargement and sulcal widening (29%) and white matter lesions (38%) were prominent findings. White matter lesions were positively correlated with HIV-1 viral load levels. In a small follow-up sub study white matter lesions did not improve while children with ventricular enlargement and sulcal widening showed improvements whilst being treated with cART. Conclusions In the current era of cART HIV-1 infected children still frequently show neurological impairments together with abnormal neuro-imaging.